STUDY OF CHLOROPHYLL-A DISTRIBUTIONS IN LOMBOK STRAIT USING BIOGEOCHEMICAL MODEL BASED ON REGIONAL OCEAN MODELLING SYSTEM (ROMS) - ANGGRAENI, KADEK ARY; Osawa, Takahiro; Arthana, I Wayan (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2012)
Regional Ocean Modelling System (ROMS) has been intended to be a multi-purpose, multi-disciplinary oceanic modeling tool. The Biogeochemical model have coupled to ROMS consists of a system of seven coupled partial differential equations that include: nitrate, ammonium, small and large detritus, phytoplanJ..'ton, zooplankton, and a dynamic phytoplanJ..-ton carbon to chlorophyll ratio. The study of distribution patterns of chlorophyll-a in Lombok Strait (-7 °N - ·10 •sand 114 "E - 117 °E) in 2006 was analyzed using the Biogeochemical model based on ROMS. The results show that low chlorophyll-a distributions (0.20 mgChl-a/m3) observed in Lombok Strait in ,January. Chlorophyll-a estimated around the southern part of Bali Strait and low chlorophyll-a distribution in upper layer of the Lomhok Strait. Chlorophyll-a of the booming (0.32 mgChl-a/m3) observed in August. The northeast current direction moves to the west and southern part of research area through Lombok Strait. The highest chlorophyll-a concentration estimated in the northern and southwestern part of Bali Tsland and also in the southern part of Lombok Island. During dry monsoon, southeasterly wind blow from Australia generates upwelling process (low temperature and nutrient-rich water near the surface) also estimated from ROMS.
Keywords: Biogeochemical model, Regional Ocean Modelling System, chlorophyll-a distributions, upwelling process